DIRECTIVE ACTS FOUND IN ENGLISH TEACHERS’ TALK IN CLASSROOM INTERACTION - Nia Kurniati; Sukarsono; Adi Saputra (Prosiding Seminar Nasional Bahasa, Sastra, Seni, dan Pendidikan Dasar (SENSASEDA), 2022)
Understanding the entire social context in every sentence uttered is needed because every language produced is not as simple as its lexical meaning but also depends on the context. The study of contextual meaning is called pragmatics. This study pragmatically attempts to analyze directive acts; which is that kind of speech acts that speaker uses to get someone else to do something. The research used descriptive quantitative which employs pragmatic analysis. It is intended to investigate types of directive acts used by English teachers’ talk in classroom interaction in Elementary level and Junior High School level, how directive acts are formally realized in both levels of education, and also how are the comparisons of the frequency of occurrences of directive acts found in both levels of education. The data are teacher’s utterances containing directive acts in Elementary level and Junior High School level, and also the reason how directive acts are formally realized and the comparisons of the frequency of occurrences of directive acts found in English teachers’ talk in SD Islam Al-Azhaar Tulungagung and SMP Islam Al-Azhaar Tulungagung. Hence, it is important to human especially teachers to use directive acts in their utterances to avoid misunderstanding in their communication and they can explore the various forms of English teachers’ talk to express one linguistic function, i.e. directive act.